Time will tell: Revisiting the impact of college expansion on income and occupational prestige mobility of young adults in Taiwan. (10th November 2020) - Kuan, Ping‐Yin; Peng, Ssu‐Chin
Abstract: The paper proposes a counterfactual analysis to estimate the causal effects of college expansion on the changes in income and occupational prestige of young people in Taiwan. The public attributes the rapid expansion of higher education in Taiwan in the mid 1990s as a significant cause of stagnant wage growth and high unemployment rates of college graduates in recent years. The primary concern in evaluating the policy consequences of educational expansion should be on those who would respond to expanded opportunities for education. In this paper, we use the data collected by the Panel Study of Family Dynamics in Taiwan to identify a pre‐expansion cohort and a post‐expansion cohort. We then use the matching method and the difference‐in‐difference (DID) model to estimate the impact of expansion on the changes in income and occupational prestige of three counterfactual groups: 'always‐takers', 'compliers', and 'never‐takers'. The results show that the impact of college expansion decreased the advantage of always‐takers and benefited compliers in both income and occupational attainment of their first job. The adverse effects of college expansion suffered by always‐takers disappeared after working for either 10 or 15 years, which fits the prediction of the signalling theory. 摘要: 本研究以反事實分析架構之角度，探討台灣高教擴張對年輕世代之薪資與職業流動的影響。本研究使用臺灣「華人家庭動態資料庫」於2003年及2009年的新增樣本及其後續追蹤調查，先配對並建構出無論高教擴張是否一定會上大學之「必為者」、順應高教擴張而有機會上大學之「順勢而為者」，以及無論高教擴張與否都不會上大學之「必不為者」等三類群體，藉此避免因擴張前後高教人口組成結構不同而無法直接比較的問題。研究結果發現，就順勢而為者言，高教擴張對其初職薪資和職業聲望有著正面影響，且持續到就業十年和十五年後；對必為者而言，高教擴張對其初職薪資和職業聲望有著負面影響，但雖著工作經驗的累積，該負面影響消失。整體而言，本文的研究成果支持訊號論的主張。